Catalytic oxidation of PAHs in wastewater = Katalityczne utlenianie WWA w ściekach - Turek, Agnieszka; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the investigations was to determine the effectiveness of the removal of 4, 5 -ring PAHs from coking wastewater using dihydrogen dioxide in the presence of a cobalt, platinum or titanium catalyst. A dose 7.4 mL of dihydrogen dioxide in the amount of and 14.8 mL/L of the analyzed sample were added to the samples. The samples were shaken and stored under laboratory conditions for 12 hours. The concentration of PAHs before and after the oxidation process were determined.
Keywords: utlenianie; H2O2; GC-MS; ścieki koksownicze; katalizator platynowy; katalizator tytanowy; WWA; oxidation; coking wastewater; platinum catalyst; cobalt catalyst; titanium catalyst; PAHs